Teaching Italian as a Foreign Language in Ungheria, from the Fall of the Berlin Wall to Today - Andreini, Anna (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
This essay is about the diffusion of Italian in Hungary starting from 1989, the year in which the obligation to learn the Russian language expires, which remained in force for 40 years, excluding all other Western languages. From that moment every alternative to the choice of Russian was preferred: multiple structures for the teaching of Italian born and there were multiple changes about the diffusion of Italian as LS, which we will expose in the following report. In addition, in this essay will be presented an analysis of the Italian LS books most used in educational institutions in Hungary with the aim of seeing to date which language model is used through them. The analysis of the manuals is part of a broader research about Italian language in Hungary and whose objectives are as follows: first, monitoring the Italian LS system in Hungary through a mapping of all the structures for the dissemination of the Italian language, going specifically to identify the type of structure, a contact person or contact for each of them, the number of students and other information. Instead, the second objective is about the analysis of the specific preparation of Hungarian teachers in the linguistic and glottodidactic field of Italian LS, the method or approach they apply in the educational institutions where Italian is taught, and finally any problems related to these two issues.